Response of Barley to Different Levels of Water Under Sprinklers in Environment Arid
The rainfed Omani barley ’Duraqui’ was studied for its response, with respect to yield and yield contributing characters. to three moisture levels under sprinklers during winter, 1995-96 at Agriculture Research Center (ARC) and Livestock Research Center (LRC), located at Rumais in South Batinah region of Sultanate of Oman. Water levels had a significant effect only for total water applied, while the location effect was significant for plant height, spike weight, grain yield and WUE (grain yield). The interaction effect between water level and location was evident for both grain al